Towards effective conservation planning: integrating landscape modelling to safeguard the future of the endangered Kashmir musk deer in the face of land use change - Sharief, Amira; Kumar, Vineet; Joshi, Bheem Dutt; Singh, Hemant; Bhattacharjee, Saurav; Dutta, Ritam; Dar, Shahid Ahmad; Ramesh, Chinnasamy; Graham, Catherine H.; Thakur, Mukesh; Sharma, Lalit Kumar (Frontiers in Ecology and Evolution, 2023)
Human expansion and anthropogenic activities are causing the conversion of forests to other land uses in the Himalayas, which is threatening species with extinction. To address this issue, we used an ensemble model to simulate the future landscape and assess its impact on the Kashmir Musk Deer (KMD) distribution in the context of land use change. Our simulation suggests a decline in croplands and shrublands and increase of mixed forests in the future scenario. Evergreen broad-leaf and needle-leaf forests are likely to convert to mixed forests, while croplands and barren areas transform into savannas. Precipitation, elevation, and mixed forests were found to be the most significant factors influencing KMD distribution. Only 20,690 km2 out of the total area of 324,666 km2 is currently suitable for KMD, but this is projected to increase to 22,701.47 km2 in the future. We predict a habitat gain of about 2,722 km2 in new areas and a loss of 711 km2 in existing habitats for KMD by 2030, with Uttarakhand state losing much of the suitable habitat. However, new habitats in future will become available for the species in Jammu and Kashmir. Our landscape configuration investigation indicates a decline in the number of patches and aggregation index in the future scenario. Most of the suitable KMD habitats are outside the current protected areas (PA), making the current PA network insufficient for long-term conservation. Therefore, we suggest forest managers to rationalize the boundary of the PAs to include suitable habitats that are currently not protected for the long-term survival of the KMD.